Dinoprostone in first trimester miscarriages: a prospective observational study in a Malaysian Tertiary Healthcare Institution - Rahana Abd Rahman,; Azarisyam Ahmad,; Ixora Kamisan Atan,; Zaleha Abdullah Mahdy, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this paper was to evaluate the outcome of medical evacuation of first trimester miscarriages using dinoprostone. A prospective observational study in a tertiary centre between 1st January and 31st December 2018 in Obstetrics and Gynaecology unit, UKM Medical Centre. Women diagnosed with incomplete and missed miscarriage (n=41) at or less than 13 weeks of gestation were recruited. Dinoprostone 3 mg was inserted into the posterior fornix, twice within 6 h apart on day-1 followed by similar protocol on day-2. Patients were reassessed clinically and sonographically upon passing out products of conception, at 48 h and day-7. Complete evacuation was defined as closed cervical os and/or endometrial thickness of less than 15 mm sonographically. Treatment failure was defined as failure to achieve complete evacuation by day-7. Overall success rate was 55.3% (n=26) being better in incomplete (n=6, 100%) as compared to missed miscarriage (n=21, 48.8%, p=0.03). Those with successful evacuation required dinosprostone at a mean of 8.4 ± 2.9 mg achieving complete miscarriage within a mean of 27.8 ± 16.6 h. Mean pain score was 5.8 ± 0.8 with mean patient satisfaction score of 8.7 ± 0.8. Mean drop in haemoglobin was 0.7 ± 0.2 g/dL. No major adverse effects were reported. Medical evacuation of miscarriage using intravaginal dinoprostone is safe and promising, with acceptable success rate and high patient satisfaction. This study supported previous studies suggesting presence of prostaglandin E2 receptors in the first trimester.